Multicriteria Decision Method for Renewable Energy Production: Siting Solar, Wind and SHP Plants in Zimbabwe - Ngwenya, Grace (School of Architecture, Planning and Geomatics, 2024)
Energy plays an enormous role in economic growth, progress, and development. The energy development in Zimbabwe has not been coincident with the rising demand of energy, placing a large strain on existing resources. Most of the energy is powered by coal-fired stations that now require major upgrades. The low-capacity problem has resulted in frequent production stops and power cuts that affect economic performance of industries and services. These power shortages have led to the formulation of the National Renewable Energy Policy (NREP), which stipulates that by 2030, Zimbabwe needs to be driven by clean and sustainable energy sources. In this regard, the government has devoted itself to achieving the Sustainable Development Goals (SDGs). The aim of the study was to identify suitable locations for renewable energy production plants in Zimbabwe. The first step in the process was to define suitability criteria for siting wind, solar and small hydro power plants. Vector and raster data sets corresponding to the criteria were gathered and a geodatabase was constructed. The process of identifying suitable areas involved the transformation of criteria values, generation of criteria-based maps, standardization, and ultimately locating the suitable energy plant sites using Multi Criteria Decision Method (MCDM). The method used to identify suitable regions for renewable energy in Zimbabwe were compared to the existing renewable resources in Zimbabwe and validated using models created for South Africa. The study demonstrates that Zimbabwe has enormous potential for wind, solar, and SHP resources, all of which have the potential to alleviate the country's severe energy shortages. Hwange Rural, which has a land area of 26 974 km2, is the best place for solar power plants. The Beitbridge Rural District, which has a land area of 12 719 km2, is the best place for small-scale utility wind power turbines. Small hydropower plants would thrive in the Gwayi and Shangani Rivers. Additionally, a thorough comprehension of the technical aspects of each renewable energy source is required. The availability of solar resources, PV module efficiency, spacing factor, and accessible land area are some examples of the information that must be gathered in order to derive the technical potential for the creation of solar PV systems. Addressing obstacles to the widespread adoption of renewable energy technologies in the country can be accomplished through the establishment of policies and regulatory frameworks.